Niepełnosprawność – INNA jakość, która ma prawo taką pozostać - Pawelczak, Katarzyna (Wydawnictwo Naukowe UAM, 2013)
Intellectual disability is characterized by below-average intelligence or mental ability and a lack of skills necessary for day-to-day living. Intellectual disability is a term used when there are limits to a person’s ability to learn at an expected level and function in daily life. We are capable of talking about a person’s l i m i t s, but if we think about a P e r s o n with a disability? The present study focuses on the question: is disability a quality, ANOTHER quality? Who is a P e r s o n with a disability? This paper aims at stimulating a debate on this topic.
Disability – ANOTHER Quality, Which May Stay As It Is
Keywords: person with an intellectual disability; Another’s perspective; Another’s perspective; quality in disability; otherness